Box-Behnken Design for Optimization of Formulation Variables for Fast Dissolving Tablet of Urapidil - Roy, Harekrishna (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the present study was to formulate the fast dissolving tablets (FDT) of urapidil by studying the effect of the variable for response with the help of Box-Behnken design (BBD). Materials and Methods: A total of 17 formulations were prepared by altering the proportion of cross carmellose sodium, spray dried lactose, and hydroxypropyl methylcellulose K4M by direct compression technique. BBD was employed to study the relations among the variables and to statistically optimize the formulation parameter for FDT tablets of urapidil. Furthermore, the powder mixture characteristics and tablet physiochemical properties such as hardness, friability, drug content, disintegration time (DT), and dissolution test were performed using 900 ml of 0.1N HCl (pH-1.2) at 37 Â± 0.5Â°C. Results: BBD successfully provided the significant value for the quadratic model and second order polynomial equation was plotted. Response surface and contour plots were plotted based on BBD and relationship between the variables and response (DT) were established. A perturbation graph was also plotted to identify the deviation of viable from the mean point. An optimized model was prepared based on predicted response, and the resulted response (DT) was close with the predicted value. Conclusion: Thus, it can be concluded that the optimized formulation with desirable parameters can be obtained by BBD with the response and variable relation. This study can be implemented and could be used in the large experiment with the involvement of a large number of variables and responses.